2019
DOI: 10.1101/756262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computer vision to automatically assess infant neuromotor risk

Abstract: An infant's risk of developing neuromotor impairment is primarily assessed through visual examination by specialized clinicians. Therefore, many infants at risk for impairment go undetected, particularly in under-resourced environments. There is thus a need to develop automated, clinical assessments based on quantitative measures from widely-available sources, such as video cameras. Here, we automatically extract body poses and movement kinematics from the videos of at-risk infants (N=19). For each infant, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Finally, the most popular algorithms for movement classification are currently SVMs, Random Forests and CNNs, due to their simplicity and straightforward application for a large variety of problems. Novel algorithms have been introduced to the field of automated GMA, such as the Naive Gaussian Bayesian Surprise (NGBS), applied to calculate how much each infant’s movements in a dataset deviate from a group of typically developing infants as the indicator of risk for atypical GMs ( Chambers et al, 2019 ). Similar as in choosing the suitable sensing setups, the selection of the most appropriate algorithm is also contingent on, among others, the data acquisition approaches, the dataset characteristics, and the goal of classification and detection.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the most popular algorithms for movement classification are currently SVMs, Random Forests and CNNs, due to their simplicity and straightforward application for a large variety of problems. Novel algorithms have been introduced to the field of automated GMA, such as the Naive Gaussian Bayesian Surprise (NGBS), applied to calculate how much each infant’s movements in a dataset deviate from a group of typically developing infants as the indicator of risk for atypical GMs ( Chambers et al, 2019 ). Similar as in choosing the suitable sensing setups, the selection of the most appropriate algorithm is also contingent on, among others, the data acquisition approaches, the dataset characteristics, and the goal of classification and detection.…”
Section: Discussionmentioning
confidence: 99%
“…In another paper, Olsen et al [ 19 ] presented a model-based approach for tracking infants in 3D. A Deep Learning-based approach [ 36 ] is also used on the dataset built upon YouTube videos. The hybrid approaches have also been experimented by incorporating the features extracted from motion and visual data [ 32 ] and implemented the motion segmentation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Deep Learning for Pose Estimation: Chambers et al [ 36 ] built a Convolutional Neural Network to extract the pose of infants. They were the only ones to publish an unsupervised approach as preprint and showed that they can distinguish unhealthy movement from infants based on an NB classifier exclusively trained on healthy children.…”
Section: Methodology Of the Reviewed Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest publications in the field of computer-aided diagnostics of infants indicate the direction of further development towards solutions based on human pose estimation algorithms [ 26 , 27 ]. The results of the research using this approach show the great potential of the OpenPose library for this type of application [ 28 , 30 , 36 ].…”
Section: Discussionmentioning
confidence: 99%